Social work in health care in the 21st century - Dhooper, Surjit Singh. 4 0 16; 5 (Thousand Oaks : Sage Publications, 1997)
This book demonstrates how, in the rapidly evolving and often uncertain health-care industry, the role of social work will become increasingly significant. Social workers will have new opportunities to help improve the health of individuals, families and communities. Focusing on four major health-care domains - acute care, ambulatory care, illness prevention//health promotion and long-term care - the author provides social workers with current, comprehensive information about the roles they can play and the skills they need in all aspects of health care. The book reviews the past and present of each of these fields, projects their major needs in the future, and identifies how social work can help to meet those needs.
1. Introduction -- A brief look at social work and health care -- Forecasting the future of health care -- Likely-to-persist health and health-related problems -- Significance of the changing health care scene for social work -- Social work assets for future roles in heath care -- 2. Heath care settings: their past -- Acute care settings -- Ambulatory care settings -- Illness prevention and health promotion agencies -- Long-term care settings -- 3. Future needs of health care -- Future needs of acute care settings (hospitals) -- Future needs of ambulatory care settings -- Future needs of illness prevention and health promotion agencies -- Future needs of long-term care facilities -- Future needs of health care providers across settings -- 4. Social work in acute care -- History of social work in acute care settings -- Future social work roles in acute care settings -- Social work knowledge and skills -- 5. Social work in ambulatory care -- History of social work in ambulatory care settings -- Future social work roles in acute ambulatory care settings -- Future social work roles in nonacute ambulatory care settings -- Social work knowledge and skills -- 6. Social work in illness prevention and health promotion -- History of social work in illness prevention and health promotion -- Future social work roles in illness prevention and health promotion -- Social work knowledge and skills -- 7. Social work in long-term care -- History of social work in long-term care settings -- Future social work roles in long-term care settings -- Social work knowledge and skills -- 8. Thriving in health care -- Worker-focused strategies -- Other strategies.
Includes bibliographical references (p. 327-364) and indexes.
Keywords: 2 -- 0; 6; Medical social work. -- 20; 20; 2